Self-perceptions of aging: a conceptual and empirical overview - Diehl, Manfred; Wahl, Hans-Werner (Current opinion in psychology, 2024)
This article defines self-perceptions of aging (SPA) as individuals' perceptions, expectations, and experiences regarding their own process of growing old(er). As such, SPA are considered a critically important element of the aging self. Furthermore, the authors present a heuristic model that positions adults' SPA within a lifespan developmental and cultural-societal context and elaborates distal and proximal antecedents, process modes, and developmental outcomes. The remainder of the article summarizes recent empirical findings and discusses future challenges and directions.